Non-uniform stagnant motions of materially non-uniform simple fluids - Zahorski, S. (Archives of Mechanics, 1996)
Non-uniform stagnant motions of materially non-uniform (inhomogeneous) incompressible fluids are reconsidered in greater detail. These motions may be used in many practical situations, such as fibre spinning and drawing processes. It is shown that the corresponding constitutive equations are very similar to those describing motions with constant stretch history or, in particular, steady extensional flows.